2020
DOI: 10.22579/20112629.587
|View full text |Cite
|
Sign up to set email alerts
|

Captura de carbono en biomasa de sistemas de uso del suelo, municipio de Yopal, Casanare, Colombia

Abstract: El cambio climático, ocasionado por el incremento en la concentración de gases efecto invernadero (GEI), genera alteraciones en el clima del planeta, aumentando la temperatura media global, lo que afecta patrones de precipitación. El área de estudio se ubicó en el Municipio de Yopal, corregimiento Tacarimena, compuesta por ocho veredas, la cual presenta clima cálido – húmedo con promedio de precipitación anual de 2270 mm; temporada seca de diciembre-marzo y lluviosa de abril-noviembre y alturas inferiores a 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…This was confirmed in the present research, because animals have more options to select higher quality feed when they have more forage area, which would reduce methane emissions (Gutiérrez Bermúdez and Mendieta Araica, 2022). Numerous studies (López-Santiago et al, 2019;Carvajal and Andrade, 2020;Yunga, 2020), have confirmed that the use of SPS contributes to reducing GHG emissions from livestock farms. Here, we found that this reduction was on the order of 17%, which is a considerable step toward achieving the goals of returning to livestock as a mitigator of climate change (Schettini et al, 2021;Gutiérrez Bermúdez and Mendieta Araica, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…This was confirmed in the present research, because animals have more options to select higher quality feed when they have more forage area, which would reduce methane emissions (Gutiérrez Bermúdez and Mendieta Araica, 2022). Numerous studies (López-Santiago et al, 2019;Carvajal and Andrade, 2020;Yunga, 2020), have confirmed that the use of SPS contributes to reducing GHG emissions from livestock farms. Here, we found that this reduction was on the order of 17%, which is a considerable step toward achieving the goals of returning to livestock as a mitigator of climate change (Schettini et al, 2021;Gutiérrez Bermúdez and Mendieta Araica, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…In Colombia, taxes and emission reduction goals can achieve significant reductions of CO 2 (Calderón et al, 2016). For example, it is possible to include carbon sequestration and storage in forests (Carvajal and Andrade, 2020;Segura-Madrigal et al, 2020) and agroforestry systems with cacao (Somarriba et al, 2013;Marín et al, 2016). In this context, these estimations provide elements for a carbon project proposal, such as those REDD+ (Lee and Pistorius (2015) that grant a benefit to local inhabitants.…”
Section: Value To Pay For the Ecosystem Services Of Carbon Sequestration And Storagementioning
confidence: 99%
“…The mean biomass of the examined trees was utilized to calculate the overall fresh biomass per hectare by multiplying this figure by the total number of trees [54]. To establish the total C storage in the systems, the values of carbon stored in the aerial biomass, including stem, coarse roots, and soil, were added together [30,55,56]. The C present in the biomass was considered to be 50% when following the method proposed by [57].…”
Section: Estimation Of Carbon Storagementioning
confidence: 99%